FDI Led Growth Hypothesis and Export Led Growth Hypothesis in ASEAN - Alvin Sugeng Prasetyo; Mochammad Devis Susandika (UPT Penerbitan Universitas Jember, 2022)
Economic growth is a macroeconomic variable that is always the government's attention. This is because economic growth is an indicator of a country's economic performance. If economic growth grows high, then economic development goes well, so that people are more prosperous. This study aims to examine and analyze the role of FDI and exports on economic growth in ASEAN. The research method used is a causality panel with a research period of 2010-2020. The causality panel used in this study detects how the relationship between FDI, exports, and economic growth in ASEAN is. The estimation results show a unidirectional relationship between FDI to economic growth, and exports to economic growth. Therefore, the hypothesis of FDI led growth and export-led growth is acceptable. The recommendation given to each country is that it is hoped that the governments of the ASEAN region will further facilitate foreign investment permits by means of deregulation that makes it difficult for foreign investors. Recommendations related to exports are that the governments of each ASEAN country need to map out potential and non-potential exports, if potential exports are increased, while non-potential ones need to be innovated.